Sistem Pengendalian Persediaan Stok Barang Pada Toko Hafiz Menggunakan Metode EOQ (Economic Order Quantity) - Tyka Makhfiroh; Mugiarso; R. Wisnu Prio Pamungkas (Journal of Students‘ Research in Computer Science, 2022)
Inventory control needs to be considered by retail and manufacturing companies because it greatly determines the smooth running of business activities in achieving maximum profits with minimal costs. Inventory management of the Hafiz Store is still done manually. This can be overcome by having a prediction of the inventory that must be done to meet the number of customer requests. Prediction is expected to determine the optimal inventory. So the use of the Economic Order Quantity method in predicting demand for the next period is the right choice. The results of the analysis of yarn inventory control at the Hafiz Store concluded that the average demand for raw materials was 100 with an order cost of 1000, and a storage cost of 1000, with a period of 5 days, and the reorder point was 2550, the EOQ results obtained were 55. The prediction results are obtained then the process the calculation of the Economy Order Quantity (EOQ) method which is used to determine the number of items that must be ordered for each order, the amount of safety stock, and the minimum amount of stock for reordering through the built inventory application. Keywords: Economy Order Quantity, Inventory Control   Abstrak Pengendalian persediaan perlu diperhatikan oleh perusahaan retail maupun manufaktur karena sangat menentukan kelancaran kegiatan usaha dalam mencapai keuntungan sebesar-besarnya dengan biaya seminimal mungkin.  Pengelolaan persediaan Toko Hafiz masih dilakukan secara manual Hal itu dapat diatasi dengan adanya suatu prediksi terhadap persediaan yang harus dilakukan untuk memenuhi jumlah permintaan pelanggan. Prediksi diharapkan dapat menentukan persediaan yang optimal. Sehingga penggunaan metode Economic Order Quantity dalam prediksi permintaan periode selanjutnya merupakan pilihan yang tepat. Hasil analisis pengendalian persediaan benang pada Toko Hafiz diperoleh kesimpulan yaitu, permintaan rata-rata bahan baku 100 dengan biaya pesan 1000, dan biaya simpan 1000, dengan periode 5 hari,dan Reorder point 2550  maka hasil EOQ yang didapat 55. hasil prediksi didapatkan maka proses perhitungan metode Economy Order Quantity (EOQ) yang digunakan untuk menentukan jumlah barang yang harus dipesan untuk setiap pemesanan, jumlah persediaan pengaman, dan jumlah stok barang minimal untuk melakukan pemesanan kembali melalui aplikasi inventory yang dibangun. Kata kunci: Economy Order Quantity, Pengendalian persediaan